Environmental Technology: Potential of Merging Road Pavement with Stormwater Detention - Yau, Darrien Seng Mah; Putuhena, F.J.; Nor Azalina, Rosli (JASPE, 2014)
This study stresses on the concept of multi-functional urban land use incorporating permeable pavement integrated with underground storage. Permeable pavement that is available in the market consists of pavers and a thick layer of course aggregates that store water. Contrary to the mentioned pavement, this study tries to replace the underlying storage with blocks of concrete detention cells. Stormwater permeates through the openings of pavers and flows into the detention storage underneath. Investigation of such application is carried out using the SWMM software. Performance of a single hollow cube pavement block (0.25m x 0.25m x 0.25m) is demonstrated here. The block is virtually subjected to the worst scenarios of extreme rainfalls over a non-stop time span of three hours. Modelling outputs point to encouraging benefits of the anticipated size and storage volume are capable of capturing stormwater up to at least one hour. Thus, the system is suggested to be effective in limiting stormwater, and subsequently, promoting road structure as multi-purpose infrastructure.